Physiological Proteins in Therapeutics: A Current Review on Interferons - Ghosh, Debosree; Ghosh, Debjani; Parida, Pratap (Mini Reviews in Medicinal Chemistry, 2016)
Interferons are produced in vivo and are one of the prime components of natural defense system of animals. They are released by the viral infected cells and provide protection to the neighboring cells against viral infection. The cyto-protective property of the proteins ignited the thought of their pharmaceutical adaptation for therapeutic use against viral diseases in individuals in whom the interferons released naturally are not sufficient to combat the situation. Interferon supplements have been found to complement various antiviral drugs. Considering the efficacy of interferons in regulating angiogenesis and immunomodulation, they can be adapted for therapy of the killer diseases like cancer and AIDS. We have come ahead more than twenty five years after the approval of clinical use of interferon as drugs and are today really in a position to promise a disease free life to our present and next generation. Interferon therapy will be contributing a big share to the upcoming remedies for the new diseases and we are thus armed to fight back the deadly viral threats. Interferons have been modified [pegylated etc.] and have already been adapted to some extent in certain diseases and are in regular use in some. Thus interferons if modified as per need and used in combination with either antiviral drugs, antibiotics, antioxidants may strengthen our defense system effectively to bring about a strong protection against wide range of diseases.
Keywords: Angiogenesis